Stripping moulds from ingots in Bessemer mill (Underwood & Underwood)
View of pig iron ingots being stripped from their molds in a Bessemer mill at an unknown manufacturing plant. The Bessemer mill takes its name from the "Bessemer process," an inexpensive industrial method for the mass-production of steel from molten pig iron. This photograph is one of a set of fourteen stereographs detailing the production of iron and steel by various processes.
Keywords: Iron industry and trade; Steel industry and trade; Bessemer process; Manufacturing industries